Work-Life Balance of Employees: An Organizational Context of Middle East - Thomas, Basil John (International Journal of Psychosocial Rehabilitation, 2020)
The imbalance between working hours and personal hours with reduction in the later has emphasized on the importance of the work-life balance programs that can facilitate employees to maintain balance and address conflicts of demands from workplace and personal and social life. After a decade passed, and many economies recovering from the economic downturn, it is important to explore whether the pressures on work-life balance has reduced and if companies are now resuming to increase facilities for employees in terms of work-life balance. Within this context, this study aimed to investigate work-life balance of employees in the Middle East countries and to explore the role of local businesses in facilitating employees to maintain work-life balance. Within the quantitative framework, a survey was conducted among 308 employees to explore their perception about work-life balance and support from their employers to achieve work-life balance. The results indicate that the work-life balance of employees is disturbed. There is increased workload, long working hours which in turn cause stress and tiredness. The employees are unable to manage family and social life and maintain adequate level of leisure and sporting activities even though sport and leisure activities are less important concern of employees. The research also concludes that there is high rate of employee turnover intention. Furthermore, there is also lack of support from Middle East employers. Employees are not engaged and involved in determination of work load and work schedules. There is also a need to improve leave and vacation policies. The SEM results indicate that employees in the organizational context are mainly concerned with time for family and social surroundings, changing their jobs if their current employers do not meet their requirements, longer working hours, and determination to their job tasks even though it is not necessary sometimes.